2013
DOI: 10.1177/0748233713511512
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent genotoxicity of copper oxide nanoparticles stimulated by reactive oxygen species in human lung epithelial cells

Abstract: Copper oxide nanoparticles (CuO NPs) are of great interest in nanoscience and nanotechnology because of their broad industrial and commercial applications. Therefore, toxicity of CuO NPs needs to be thoroughly understood. The aim of this study was to investigate the cytotoxicity, genotoxicity, and oxidative stress induced by CuO NPs in human lung epithelial (A549) cells. CuO NPs were synthesized by solvothermal method and the size of NPs measured under transmission electron microscopy (TEM) was found to be aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(53 citation statements)
references
References 58 publications
(59 reference statements)
3
48
0
2
Order By: Relevance
“…Studies on astrocytes [17] and other cell types [12,13,[49][50][51][52] revealed that CuO-NP-treated cells suffer from an increased formation of cellular ROS. For astrocytes, elevated ROS levels and toxicity were prevented by coapplication of the membrane-permeable copper chelator TTM, suggesting that copper ions which have been liberated from the accumulated CuO-NPs are responsible for the ROS-induced toxicity [17].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on astrocytes [17] and other cell types [12,13,[49][50][51][52] revealed that CuO-NP-treated cells suffer from an increased formation of cellular ROS. For astrocytes, elevated ROS levels and toxicity were prevented by coapplication of the membrane-permeable copper chelator TTM, suggesting that copper ions which have been liberated from the accumulated CuO-NPs are responsible for the ROS-induced toxicity [17].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study also demonstrated that CuO NPs (average size: 53 nm) regulated the genes involved in DNA damage and apoptosis (e.g., Hsp70, p53, Rad51 and MSH2) [34]. Another recent study from our group observed that CuO NPs (average size: 23 nm) induced dose-dependent (5-15 μg/ml) cytotoxicity, DNA damage (comet assay) and micronuclei induction in A549 cells [35].…”
Section: Lung Toxicity Of Cuo Nanoparticles: In Vitro Studiesmentioning
confidence: 92%
“…Once the NPs were introduced to aqueous media, the sizes changed to often times higher than those of the primary size [33]. For example, our previous studies have shown that, once CuO NPs are introduced into cell culture media, their hydrodynamic sizes changed to around ten-times higher than those observed from CuO nanopowder [34,35]. The higher size of CuO NPs in aqueous suspension compared with the primary size of dry powder might be due to the tendency of particles to agglomerate in an aqueous state.…”
Section: Physicochemical Characterization Of Cuo Nanoparticles Beforementioning
confidence: 93%
“…[1][2][3][4][5][6][7][8][9][10] Although in the vast nanotoxicological literature of the last decade studies concerned with the assessment of metal or metal-oxide NP toxicity are not at the top of the list, such publications are nevertheless quite numerous. To illustrate this, we may refer to several works devoted to NPs of the metals that were the subject-matter of our own studies considered below: iron oxide, [11][12][13][14][15][16][17][18][19][20] silver, gold, 24,[45][46][47][48][49][50][51][52][53][54][55][56][57][58] copper and copper oxide, 43,[59][60][61][62][63][64][65][66][67][68] nickel oxide, 65,[69]…”
mentioning
confidence: 99%